2021
DOI: 10.1039/d1sm00246e
|View full text |Cite
|
Sign up to set email alerts
|

Loading and relaxation dynamics of a red blood cell

Abstract: We use mesoscale numerical simulations to investigate the unsteady dynamics of a single red blood cell (RBC) subjected to an external mechanical load. We carry out a detailed comparison between...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
3
15
0
Order By: Relevance
“…Liu et al [61] developed a coupled IBM-LBM with an absolute nodal coordinate formula and acceleration techniques to simulate large deformation in complex multiple flexible immersed structures. Guglietta et al [62,63] coupled the IB-LBM with the standard linear solid model to account for the red blood cell membrane viscosity. As for the rigid moving boundaries, researchers used various approaches to spread the IB force over fluid nodes by means of the Dirac delta function.…”
Section: Numerical Methods For Particle-fluid Hydrodynamicsmentioning
confidence: 99%
“…Liu et al [61] developed a coupled IBM-LBM with an absolute nodal coordinate formula and acceleration techniques to simulate large deformation in complex multiple flexible immersed structures. Guglietta et al [62,63] coupled the IB-LBM with the standard linear solid model to account for the red blood cell membrane viscosity. As for the rigid moving boundaries, researchers used various approaches to spread the IB force over fluid nodes by means of the Dirac delta function.…”
Section: Numerical Methods For Particle-fluid Hydrodynamicsmentioning
confidence: 99%
“…In particular, Barthès-Biesel (2016) considered a capsule with membrane viscosity under simple shear flow, and they observed that the response (loading) time made dimensionless via the intrinsic time decreases with the capillary number. Moreover, Guglietta et al (2020Guglietta et al ( , 2021b studied the transient dynamics of RBCs under simple shear flow and in order to compare their numerical results against experiments, they reported the characteristic loading and relaxation times (in [s] on the y-axis) as functions of the shear rate γ (in [s −1 ] on the x-axis). We therefore decided to take this as an example, and to normalise both x-and y-axis with the capillary time t * , thus obtaining the dimensionless loading time t L as a function of the capillary number Ca.…”
Section: Simulation Set-up and Physical Parametersmentioning
confidence: 99%
“…The mechanical and rheological properties of suspensions of purely elastic capsules have been thoroughly studied analytically (Barthès-Biesel & Rallison 1981;Barthès-Biesel 1980, 1991, 1993Barthès-Biesel, Diaz & Dhenin 2002), experimentally (Chang & Olbricht 1993;Walter, Rehage & Leonhard 2001) and numerically (Pozrikidis 1995;Ramanujan & Pozrikidis 1998;Diaz, Pelekasis & Barthès-Biesel 2000;Dodson & Dimitrakopoulos 2009;Clausen & Aidun 2010;Bagchi & Kalluri 2011;Clausen, Reasor & Aidun 2011;Krüger, Varnik & Raabe 2011;Pranay, Henríquez-Rivera & Graham 2012;Cordasco & Bagchi 2013;Karyappa, Deshmukh & Thaokar 2014;Krüger, Kaoui & Harting 2014;Rorai et al 2015;Alizad Banaei et al 2017;Kessler, Finken & Seifert 2008;Tran et al 2020;Wouters et al 2020;Aouane, Scagliarini & Harting 2021;Bielinski et al 2021;Esposito et al 2022). However, only a few studies were dedicated to understanding the effect of the capsules' membrane viscosity (Barthès-Biesel & Sgaier 1985;Diaz, Barthès-Biesel & Pelekasis 2001;Yazdani & Bagchi 2013;Li & Zhang 2019;Guglietta et al 2020Guglietta et al , 2021aZhang et al 2020;Guglietta et al 2021b;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Guglietta et al performed a detailed comparison of loading and unloading dynamics with three different typologies of load, namely stretch, shear, and elongational flow, while changing the membrane viscosity of the cell. 33 They concluded that the time asymmetry of loading and unloading processes is profound in shear flows and increases on higher load strengths.…”
mentioning
confidence: 99%